2013
DOI: 10.1159/000355733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Degree of Obesity on Achieving Target Blood Pressure and Metabolic Deterioration in Obese Individuals: A Population-Based Study

Abstract: Background/Aims: This study aimed to evaluate the severity of obesity and its impact on achieving target blood pressure and metabolic derangement in obese individuals. Methods: This cross-sectional and population-based study was conducted between January and December 2012. A total of 1837 consecutive obese patients admitted to our outpatient clinic were enrolled. The anthropometric and blood pressure measurements, bioelectrical impedance fat analysis, blood sample analysis, impaired glucose status, metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Although the expected differences found when comparing the two groups of participants, 15–17,27,35,38,39 the main interesting findings of the present study reside in the differences found in terms of olfactory testing and biochemical assays between subjects affected by stage I and II obesity (Table II, III, Fig. 1).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Although the expected differences found when comparing the two groups of participants, 15–17,27,35,38,39 the main interesting findings of the present study reside in the differences found in terms of olfactory testing and biochemical assays between subjects affected by stage I and II obesity (Table II, III, Fig. 1).…”
Section: Discussionmentioning
confidence: 50%
“…8,9 Although many of these notions have been demonstrated when comparing obese individuals with normal weight participants, 1,[10][11][12][13][14][15] less is known regarding possible differences reflecting the different degrees of obesity in terms of olfactory sensitivity and its relationship with nutritional habits, circulating levels of modulators of feeding and olfactory behavior, anthropometic measures, and metabolic assays. Further, obesity stages-according to body mass index (BMI)-have been well correlated with different risks of metabolic deterioration, mortality, and survival 16,17 and to be implicated in dietary preferences. 18 Thus, the aim of the present study was to evaluate the differences in olfactory sensitivity, nutritional habits, circulating levels of modulators of feeding and olfactory behavior, anthropometic measures, and metabolic assays between two groups of participants with stage I and II obesity and reciprocal relationships between these parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…результаты регистра рекваЗа (регистр кардиоваскулярных Заболеваний) с участием 3690 больных в возрасте 66,1 года c аГ, иБс, хсН, фибрилляцией предсердий и их сочетаниями также показали, что у больных с ранним развитием ссЗ значимо чаще выявлялось ожирение [22]. аналогичные данные представлены в работах и других исследователей [23][24][25].…”
Section: ðåçóëüòàòûunclassified
“… 7 9 Furthermore, the severity of obesity was significantly correlated with the failure to achieve target BP. 10 Therefore, it is essential to develop therapeutic strategies to effectively manage BP in the overweight and obese population.…”
Section: Introductionmentioning
confidence: 99%